2020
DOI: 10.1101/2020.12.13.20248147
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of Mortality and Aspirin Prescription for COVID-19 Patients at the Veterans Health Administration

Abstract: There is growing evidence that thrombotic and inflammatory pathways contribute to the severity of COVID-19. Common medications such as aspirin, that mitigate these pathways, may decrease COVID-19 mortality. This assessment was designed to quantify the correlation between aspirin and mortality for COVID-19 positive patients in our care. Data from the Veterans Health Administration national electronic health record database was utilized for the evaluation. Veterans from across the country with a first positive C… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 18 publications
0
37
0
Order By: Relevance
“…Antiplatelet therapy may have beneficial effects in severe COVID-19 through several mechanisms including inhibition of platelet aggregation, reduction of platelet-derived inflammation, blocking thrombogenic neutrophil extracellular traps, and reducing disseminated intravascular coagulation. Low-dose aspirin has been used as a line of therapy, and several observational studies have reported that aspirin is associated with a reduced risk of adverse outcome in COVID-19 (58, 59). In line with oral anticoagulants, premorbid treatment with platelet inhibitors was associated with a reduction in the risk of contracting critical COVID-19 but not influenza in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Antiplatelet therapy may have beneficial effects in severe COVID-19 through several mechanisms including inhibition of platelet aggregation, reduction of platelet-derived inflammation, blocking thrombogenic neutrophil extracellular traps, and reducing disseminated intravascular coagulation. Low-dose aspirin has been used as a line of therapy, and several observational studies have reported that aspirin is associated with a reduced risk of adverse outcome in COVID-19 (58, 59). In line with oral anticoagulants, premorbid treatment with platelet inhibitors was associated with a reduction in the risk of contracting critical COVID-19 but not influenza in our study.…”
Section: Discussionmentioning
confidence: 99%
“…of thrombotic events, extracorporeal oxygenation, and mortality. 143 In addition, recent results from REMAP-CAP, ACTIV-4a, and ATTACC trials showed that an initial strategy based on therapeutic dose of heparin improved survival of non-critically ill patients and reduced the use of cardiovascular or respiratory support compared to usual-care thromboprophylaxis 144 but did not improve outcomes in critically ill patients. 142…”
Section: Anticoagulationmentioning
confidence: 99%
“…A retrospective analysis has recently emphasized that, among COVID-19-positive veterans, pre-diagnosis aspirin prescription was associated with a 2-fold decrease in 14-day and 30-day overall mortality. 143 Although the results of ACTCOVID19 (NCT04324463)…”
Section: Inhibitors Of Platelet Functionmentioning
confidence: 99%
“…Nevertheless, IL‐6 inhibitors are being trialed; several of these also may have inherent antiviral activity [292] . Several other treatments have been proposed to suppress the principal symptoms of the disease, such as aspirin (shown to have little clinical effect in a study of 183 patients in China, [293] although pre‐existing aspirin prescription was found to decrease mortality), [294] tocizumab, [295] an immunosuppressive, and colchicine, an anti‐inflammatory molecule used to treat gout [256] (initial patient data indicate a positive response in mild to severe CoVID‐19 cases) [296] . Oxidative stress is an important contributing factor to serious CoVID‐19 cases and there are reports that CoVID‐19 infection may suppress cellular antioxidant response [297] .…”
Section: Other Hypothesesmentioning
confidence: 99%